Teaching and learning to write in the University: When the reviewers are the peers - Manuela Martínez-Lorca; Carmen Zabala-Baños (Universitat Politècnica de València, 2015)
Academic  writing  in  higher  education  is  a task that must to be learn and teach for to access to the knowledge. Peer assessment is  one  of  the  assessment  strategies  that can  be  used  to  enhance  the  academic writing.  The  article  target  is  present  an experience of education innovation aimed to 43 students of first the Speech Therapy Degree  from  UCLM  to  learn  and  teach the  academic  writing.  Such  intervention combined  collaborative  peer  review  with the review of the teacher of the texts that students   wrote.   A   rubric   were   applied in  order  to  analyze  the  improvements  in the  new  versions  of  the  compositions. To  analyze  the  improvements  in  the  new versions  of  the  compositions  a  rubric  was applied  in  order  to  measure  differents aspects  of  the  texts.  Results  of  the  study show   that   this   methodology   promoted the continuous revision of the text, which affected   the   quality   of   the   final   texts. Teachers    provided    more    suggestions than    peers,    however,    have    greater acceptance  rate  the  suggestions  of  peers in the knowlegde aspects. However, these suggestions  were  mainly  directed  to  the revision  of  the  formal  aspects  while  the teacher's suggestions referred, principally, to  aspects  pragmatics  (of  coherence  and cohesion  text).  This  study  show,  how  the university  students  and  teachers  can  reap benefits   from   peer   assessment   in   the teaching  and  learning  of  the  academic writing in the higher education.